Online learning in palliative care education of undergraduate medical students: a realist synthesis - Gianfranco Martucci; Jose Pereira; Csilla Busa; Carlos Centeno; Agnes Csikos; Luca Franchini; Frank Elsner; Melania Raccichini; Maria-Mirabela Mihailescu-Marin; Daniela Mosoiu; Sandra Rubio Bernabé; Alexandra Scherg; et al. (Palliative Care and Social Practice, 2023)
Background: Although training in palliative care (PC) is increasingly frequent in medical schools, some barriers still hamper the design and implementation of effective educational programs. Information Technology-based distance learning (IT-DL) might contribute to the development of appropriate knowledge on PC in students, but it is still not clear how to best develop such curricula and how to deliver methodologically sound learning activities, allowing students to work on the complex skills required in PC. Objectives: To describe how internet-based education can be used in undergraduate medical PC education, in terms of realist theorization. Design: A realist review was carried out, producing a framework – or, in the terms of a realist review, a theory – focusing on finding out what might work, for whom, and in which circumstances, describing these variables in terms of Contexts, Mechanism, and Outcomes. Methods: An international group of experts of PC education assessed the relevance and pertinence of 256 articles resulting from systematic retrieval of literature and expert suggestions. Results: The final synthesis, mainly informed by the 43 articles rated as most relevant, is presented in propositions regarding three groups: (1) Educational theory, where (a) Cognitivism (learning as an increase in knowledge); (b) Constructivism (learning as a social, cultural, and negotiated process); and (c) Behaviorism (learning as an observable modification of behaviors) appear to be consistent with the learning outcome of PC. (2) Desired effect of the technology, suggesting the simple use of IT-DL is not an additional value per se , as it should overcome objective limits set for face-to-face activities. (3) Contextualization and duration of the curricular activity, suggesting PC training activities should be included in an organic and legitimate way in the overall curriculum. Conclusion: This field is expected to experience huge growth soon, and present and future research could use a realist approach like the one here presented to make sense of all the different variables involved.